Klasifikasi Tanaman Jeruk Berdasarkan Fitur Tekstur Daun Menggunakan Metode K-Nearest Neighbor - Andi Yulia Muniar (Celebes Engineering Journal, 2019)
The classification system built is a system that aims to facilitate the process of recognizing or introducing citrus plants with various characteristics or features found in citrus leaves. The process is carried out by taking pictures of orange leaves and then using k-Nearest Neighbor (KNN) with Euclidean distance calculations based on leaf features so as to produce conclusions from the type of citrus plant. Image data taken are samples of grapefruit leaves, lime and kaffir lime leaves. The highest accuracy result is obtained at parameter k=1 which is 81.48%.